Digital Transformation in Education in the Post-Pandemic Covid-19: Bibliometric Analysis (2020-2025) - Dewi Cahyani; Aminudin (Journal of General Education and Humanities, 2025)
This study explores the digital transformation in education accelerated by the COVID-19 pandemic using a bibliometric analysis of 1,300 Scopus-indexed publications from 2020–2025. Using the keywords “digital” AND “transformation” AND “education.” Analyzed using VOSviewer, Biblioshiny, and Microsoft Excel, and OpenRefine. The study identifies publication trends, prolific authors, institutions, and key research themes. The results show a surge in research on human-centered e-learning, innovation, and digital transformation. China tops the list with 83 articles, indicating high contributions, while the University of Oxford tops the list with the most contributions, with 28 articles. The Financial University, Under the Government of the Russian Federation, follows with 27 articles. The study emphasizes the importance of international collaboration and recommends further investigation into the socio-pedagogical implications of digital adoption in diverse educational contexts.